Confirmación diagnóstica de las metástasis pleurales y pulmonares en pacientes con antecedentes de cáncer primario conocido - Montes-Arcon, Pablo Salomón (Revista Médica de Risaralda, 2022)
Analyzing the impact of precision diagnosis in the clinical behavior of patients with pleural effusion of neoplastic origin, the study of pathological anatomy and the use of immunohistochemistry techniques are considered mandatory, which make an adequate characterization of the lesions, in order to establish a joint oncological management that improves patient survival; if we take into account the multiple advances in focused chemotherapy that are available nowadays (4).